Mesenchymal Stem Cells-Derived Exosomes as Dexamethasone Delivery Vehicles for Autoimmune Hepatitis Therapy - Zhao, Jiawei; Li, Yue; Jia, Rongrong; Wang, Jinghui; Shi, Min; Wang, Yugang (Frontiers in Bioengineering and Biotechnology, 2021)
Exosomes (Exos) are nanosized vesicles (around 100 nm) that recently serve as a promising drug carrier with high biocompatibility and low immunogenicity. Previous studies showed that Exos secreted from mesenchymal stem cells (MSCs) provide protection for concanavalin A (Con A)-induced liver injury. In this study, the protective effect of Exos is confirmed, and dexamethasone (DEX)-incorporated Exos named Exo@DEX are prepared. It is then investigated whether Exo@DEX can function more efficiently compared to free drugs and naive Exos in a Con A-induced autoimmune hepatitis (AIH) mouse model. The results show that Exo@DEX efficiently improves the accumulation of DEX in AIH in the liver. These data suggest that Exo@DEX is a promising drug carrier for AIH and could have applications in other diseases.